Tingkat Kebutuhan Penduduk Terhadap Angkutan Umum Perkotaan di Kecamatan Purwodadi Kabupaten Grobogan - Ulya Meiliana Rofiatul; Hariyanto Hariyanto; Putro Saptono (Geo-Image, 2018)
This study aims: 1). Know the number of trips generated by sub-districts in units of time; 2). Knowing what percentage of society needs in using public transportation; 3). Knowing the factors that influence using public transport; 4). Know the loading factor of public transportation in Purwodadi District. Sampling technique used is Incidental Sampling method, Purpose Sampling analysis technique, percentage description, Loading Factor. This research was conducted in Kuripan Village and Candisari Village. The results of the research note that the number of trip generation from 3 points is 25.569 journey. The need of public transportation provided is 177 units of vehicles, while the field operates only 119 units of vehicles. The people who use the transportation in both villages with a percentage of 31% is 610 of the population of 2 villages. Factors that influence the public using the transport is no vehicle, safe, cheaper cost. The load factor value at all routes during peak hours is 0.2 and in non-busy hours has a load factor value of 0.18.